Role of Ethics in Sustainable Brand Development – Study Amongst University Students on the Effect of Ethical Communication by Consumer Brands in Sri Lanka on Brand Perception - Wimalana, N.; Koswatte, I. (NSBM Green University, 2021)
The present socioeconomic environment has influenced the corporates to have a significant focus on the societal and ethical commitments when developing brands. The situation is same in the context of Sri Lanka as many multinational and local conglomerates spend heavily to establish their respective consumer brands using various promotional strategies. Certain tactics used by some of them pushing the boundaries of marketing communication principles especially in the area of social marketing platforms have exposed unseen aspects of brands creating a doubt on the authenticity of what they claim. Therefore, the purpose of this study is to examine the effect of consumer’s perceived ethicality on the authenticity of the marketing claims conveyed by the consumer brands in Sri Lanka in order to sustain their brand’s position in the market. Based on the Brunk’sConsumer Perceived Ethicality (CPE) concept, the operationalization questionnaire was developed including other salient points identified through literature on the ethical considerations in marketing. The questionnaire was distributed amongst the university students in Sri Lanka and the results were compiled using descriptive analyses. Once the data was collected, they were studied through statistical analysis. Using descriptive statistics, sample data were summarized in terms of the distribution of the data (the frequency of each score on a test), the central tendency of the data (the mean to describe the average score) and the variability of the data (the standard deviation to describe how spread out the scores is). This article discusses the findings of the research and management implications including the limitations and guidelines for future studies.
Keywords: Consumer brands; Brand perception; Ethicality; Marketing communication; Sri Lanka